AN EXPLORATORY STUDY OF TOMATO MARKETING IN EAST JAVA - Andri, Kuntoro Boga; Wandschneider, Tiago Boga; Kristedy, Teddy Boga (Proceedings of the International Conference on Green Technology; Vol 6 No 1 (2015): Proceeding of International Conference on Green Technology, 2015)
Tomato is an important source of income for many vegetable farm households in East Java. These households can generally be classified as resource-poor.  This study was conducted to provide a description and analysis of the tomato marketing in East Java. Some information and analysis of the tomato chain are also provided due to the close links between tomato production and marketing. A review of existing studies, reports, and government statistics was carried out early on during the research and qualitative methods were employed for collection of primary data.  The fieldwork was carried out during December 2012 to March 2013 in using Focus group discussions (FGD) with farmers and semi-structured interviews (SSI) with producers, other chain actors, and some knowledgeable observers in Graet Malang and its tomato marketing areas in East Java. This study shows the productivity of tomato in Malang is still below the level of potential. Some production constraints encountered due endemic pests and diseases as well as quality of seed. Besides, post-harvest handling is also less of a concern because it is still traditional. Thus there are still opportunities to be able to increase the production of tomato by improving seed genetic resources and farming technologies. Government support is needed for the provision of warehouse facilities in strategic markets and improved transportation facilities to maintain the quality.